2001
DOI: 10.1016/s1074-7613(01)00245-x
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Hepatitis C Virus Infection Is Predicted by Escape Mutations in Epitopes Targeted by Cytotoxic T Lymphocytes

Abstract: CD8(+) cytotoxic T lymphocytes (CTL) are thought to control hepatitis C virus (HCV) replication and so we investigated why this response fails in persistently infected individuals. The HCV quasispecies in three persistently infected chimpanzees acquired mutations in multiple epitopes that impaired class I MHC binding and/or CTL recognition. Most escape mutations appeared during acute infection and remained fixed in the quasispecies for years without further diversification. A statistically significant increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
339
1
4

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(356 citation statements)
references
References 32 publications
12
339
1
4
Order By: Relevance
“…This phenomenon may represent an additional pivotal mechanism establishing HCV persistence [45,46]. However, in this study the question remains unresolved why CTL specific for unrelated viruses (i.e.…”
Section: Discussionmentioning
confidence: 90%
“…This phenomenon may represent an additional pivotal mechanism establishing HCV persistence [45,46]. However, in this study the question remains unresolved why CTL specific for unrelated viruses (i.e.…”
Section: Discussionmentioning
confidence: 90%
“…However, the finding that patients resolving infection showed a broader effector CTL repertoire indicates that the multispecificity could compensate the defect of CTL responses, and ultimately control the establishment of chronic infections [38][39][40][41]. Further data are clearly needed to elucidate this complex issue, principally in order to analyze the possible signals influencing the generation of multispecific CTL responses in some HCVinfected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics of HCV contribute to the marked genomic diversity of HCV, with the potential to induce viral variants that can evade immune recognition [143; 144]. Erickson et al first demonstrated immune escape from CD8+ T cell in the chimpanzee model [145]. Mutation occurred within multiple MHC class I restricted epitopes but not flanking regions of the HCV genome within the first few months of chronic infection.…”
Section: Sequence Mutationsmentioning
confidence: 99%